Perinatal Environmental Stressors and Their Role in Premature Infant Developmental Vulnerabilities - D, Dr. Chamundeeswari; Pugazhendhi, Dr. A. V.; M, Kavitha; ATMK, Anusha (Adolescência e Saúde, 2026)
Background: Premature infants are highly susceptible to environmental influences during the perinatal period. Exposure to environmental stressors such as maternal psychological stress, air pollution, noise, socioeconomic adversity, and inadequate prenatal care can negatively affect fetal growth and neonatal development. These stressors may contribute to developmental vulnerabilities and long-term health complications in preterm infants. Objective: To assess the relationship between perinatal environmental stressors and developmental vulnerabilities among premature infants. Methodology: A retrospective observational assessment was conducted involving 120 premature infants and their mothers. Data regarding maternal environmental exposures, prenatal stress indicators, and neonatal developmental outcomes were collected from hospital records. Statistical analyses were performed to evaluate associations between environmental stressors and developmental risks. Findings: The results indicated that 42.5% of premature infants exposed to multiple environmental stressors exhibited developmental vulnerabilities. Developmental delay was observed in 34.2% of infants, while 29.1% required prolonged neonatal intensive care unit (NICU) support. Infants exposed to high maternal stress and environmental pollution demonstrated significantly lower developmental assessment scores compared with those with minimal exposure. The predictive model achieved an overall accuracy of 82.3% in identifying infants at increased developmental risk. Conclusion: Perinatal environmental stressors significantly contribute to developmental vulnerabilities in premature infants. Early identification of environmental risk factors and targeted intervention strategies may improve developmental outcomes and reduce long-term morbidity among preterm populations.